Incidencia de las actividades del laboratorio de microbiología ambiental del área agroindustrial de la ESPAM MFL en la seguridad y salud ocupacional de los trabajadores - Hernández García, Cristina Gimabel (2015)
This research was aimed at evaluating the incidence of work activities at the environmental and microbiology laboratory of the agroindustrial department at ESPAM MFL university in relation to the occupational safety and health of the staff. This research was designed as a non-experimental study. scientific and descriptive methodologies were employed. Various data collection techniques were used in order to identify the current situation of the laboratory and the staff including observation, meetings, interviews, and surveys. Furthermore, laboratory activities were identified and analysed in compliance with institutional instruments for process flowchart elaboration from the environmental and agroindustrial engineering departments, which contributed to the determination of occupational hazards to which the staff is exposed. To determine occupational risks, accidents and health hazards of the laboratory staff, the different types of hazards were evaluated through the three-step test producing results of 135 moderate risks, 211 significant risks and 61 intolerable risks. An occupational health and safety management plan was designed attending the requirements and characteristics of the environmental microbiology laboratory, founded on the occupational health and safety legislation in Ecuador, using the labor code, executive decree 2393, occupational health and safety segulation, labor environment improvement and the occupational risk insurance regulation.